Religious Beliefs and Fertility Preferences among Engaged Couples, Referring to Premarital Counseling Centers of Mashhad, Iran - Talat Khadivzade; Elham Arghavani (Journal of Midwifery & Reproductive Health, 2014)
Background & aim: Considering the lack of information regarding the effects of religion on young couples’ fertility preferences, this study aimed to evaluate the relationship between religious beliefs and fertility preferences among engaged couples in Mashhad, Iran, in 2013. Methods:This cross-sectional study was conducted on 450 engaged couples, referring to premarital counseling clinics at healthcare centers of Mashhad. Convenience sampling was applied and data were collected using Miller’s Fertility Preferences and Childbearing Questionnaires (1995), Khodayari's Religious Attitude Questionnaire, and a demographic questionnaire; all four questionnaires were completed by the participants. Spearman's correlation, Chi-square test, Mann-Whitney, and Kruskal-Wallis tests were used for data analysis. The significance level was considered to be 0.05. Results: Scores of religious beliefs were low, moderate, and high among 5.7%, 62.1%, and 32.2% of the couples, respectively. Childbearing desires (P≤0.001), ideal number of children (P≤0.001), and birth interval (P≤0.001) showed significant differences in groups with low, moderate, and high scores of religious beliefs. The mean number of children desired by the groups with low, moderate, and high religious belief scores was 2.24±1.49, 2.21±0.87, and 2.69±1.37, respectively. In total, 42.2% of the participants were moderately affected by religious beliefs. Conclusion:Fertility motivations and the ideal number of children were higher among individuals with stronger religious beliefs; however, even among these religious people, fertility preferences were not favorable, compared to figures recommended by reproductive health policymakers. These findings can contribute to the improvement of reproductive indices and fertility reforms towards higher fertility rate in the country.